2004
DOI: 10.1111/j.1463-1318.2004.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ovariectomy and hormone replacement on submucosal collagen and blood vessels of the anal canal of rats

Abstract: Oestrogen and progesterone have synergistic effects on collagen types I and III and probably antagonistic effects on the vascular plexus of the anal canal submucosa in adult female rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
4
10
0
Order By: Relevance
“…Changes in types I to III collagen ratio correlate with changes in the mechanical properties because type I is more rigid while type III contributes more to elastic properties [13]. Hence, decreased collagen I/III ratio is associated with reduced urethral and anal canal closure function [7,[13][14][15]. Both estrogen deficiency and ageing independently and negatively influences the submucosal urethral and anal canal blood vessel counts and collagen I/III ratio in anatomical, experimental and clinical studies, similar to our findings [4,11,12,14,15].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Changes in types I to III collagen ratio correlate with changes in the mechanical properties because type I is more rigid while type III contributes more to elastic properties [13]. Hence, decreased collagen I/III ratio is associated with reduced urethral and anal canal closure function [7,[13][14][15]. Both estrogen deficiency and ageing independently and negatively influences the submucosal urethral and anal canal blood vessel counts and collagen I/III ratio in anatomical, experimental and clinical studies, similar to our findings [4,11,12,14,15].…”
Section: Discussionsupporting
confidence: 77%
“…Hence, decreased collagen I/III ratio is associated with reduced urethral and anal canal closure function [7,[13][14][15]. Both estrogen deficiency and ageing independently and negatively influences the submucosal urethral and anal canal blood vessel counts and collagen I/III ratio in anatomical, experimental and clinical studies, similar to our findings [4,11,12,14,15]. In fact, ghrelin and its receptor are expressed in human microvascular endothelial cells and rat osteoblasts where ghrelin stimulates endothelial cell proliferation, migration, and angiogenesis as well as osteoblastic synthesis of collagen type I, as seen in this study [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of collagen type III in response to estrogen administration was found in hearts of aged and Dahl salt-sensitive rats (8,61). Similar estrogenic effects on collagen III were demonstrated in the arteries and other tissues of ovariectomized animals (7,10,15,24,36,47). The mechanisms of enhanced collagen type III expression due to estrogen treatment are still unknown, but they are likely related to the changes in MMPs and TIMPs expression that we Fig.…”
Section: Discussionmentioning
confidence: 60%
“…However, our data demonstrated that 28 days following PTCA or stenting, the total number of VSMC did not differ significantly from 17βE-treated segments, as compared to vehicle segments in both regions (table 1), which suggests a direct role for estrogen in the collagen synthesis/degradation process. Previous experiments reported that collagen type I increased significantly after ovariectomy and was normalized with estrogen treatment [28]. Estrogens could act on collagen expression through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%